Discharge Survey Results in the lower Mississippi River, United States of America - Kolker, Alexander; Weathers, Dallon; Christy, Swann; Alisha, Renfro (PANGAEA, 2025)
This dataset contains discharge measurements collected in the Lower Mississippi River, Louisiana, USA. Measurements were taken on the following dates: 24 May 2022, 23 August 2022, 4 April 2023, 17 April 2023, 18 April 2023, 15 May 2023, 16 May 2023, 12 June 2023, 13 June 2023, 25 July 2023, 26 July 2023, 19 September 2023, 30 January 2024, 16 February 2024, and 27 February 2024. Data were collected to determine the discharge of the Mississippi River and to assess its relationship to Neptune Pass, currently the largest new distributary of the river. Measurements were obtained using an Acoustic Doppler Current Profiler (ADCP). The data collected on 24 May 2022 and 16 February 2024 were acquired by Kolker and colleagues as part of this study, while the remaining data were collected by the U.S. Army Corps of Engineers during routine discharge surveys and shared with the authors. Additional discharge data from the USGS Belle Chasse gauge (site number 07374525) were obtained from https://waterdata.usgs.gov. The study area is located in southeastern Louisiana, with geographical bounds approximately spanning from 29.847°N, -90.023°W (northwest) to 29.129°N, -89.075°W (southeast).
Keywords: Neptune Pass